Quantification by computerized morphometry of tissue levels of sulfomucins and sialomucins in diversion colitis in rats - Martinez,Carlos Augusto Real (2010)
PURPOSE: To quantify the intensity of sulfomucin and sialomucin expression in the colon mucosa, by means of computer-assisted image processing, comparing segments with and without fecal stream and correlating with the duration of fecal transit exclusion. METHODS: Forty-five Wistar rats were subjected to diversion of the fecal stream in the left colon by means of constructing a proximal colostomy and distal mucosal fistula. They were distributed randomly into three experimental groups of 15 animals, of which 10 were subjected to colon diversion (experimental subgroup) and five were only subjected to laparotomy, without colon diversion (control subgroup). The three experimental groups were formed according to the sacrifice date, which was to be performed six weeks after the surgical procedure (Group A), 12 weeks (Group B) and 18 weeks (Group C). The sulfomucin and sialomucin expression in the colon mucosa was evaluated using the histochemical technique of high iron diamine-alcian blue (HID-AB). The tissue expression was quantified for each animal, in the segments with and without fecal stream, at a location where there were four complete contiguous crypts in two random fields, with the aid of the computer-assisted image analysis software. The final value was taken to be the mean reading from the two fields selected, in the segments with and without fecal stream. To compare the expressions of the two mucin subtypes in the segments with and without fecal stream, the paired Student t test was used. To analyze variance according to duration of exclusion, ANOVA with the Newman-Keuls post-test was used, setting the significance level at 5% (p<0.05). RESULTS: There were significant reductions in tissue sulfomucin and sialomucin content in the colon without fecal stream, independent of the duration of exclusion considered. There was increased tissue sulfomucin content and decreased tissue sialomucin in the segments without fecal stream, with increasing duration of exclusion. CONCLUSIONS: Diversion of the fecal transit decreased the tissue sulfomucin and sialomucin content in the segments without fecal stream. Notwithstanding the reduction in the levels of both subtypes of acid mucin in the segments without fecal stream, there was increased tissue sulfomucin content and decreased tissue sialomucin with increasing duration of intestinal diversion.